2017
DOI: 10.15406/jabb.2017.03.00075
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction Risk Factors and Correlation of its Markers with Serum Lipids

Abstract: Myocardial infarction is a term applied to myocardial necrosis secondary to an acute interruption of the coronary blood supply. Atherosclerosis is by far the most common cause of myocardial infarction. According to the INTERHEART study report, nine factors are responsible for 90% of myocardial infarctions. Modifiable risk factors include Diabetes mellitus, smoking, hypertension, hyperlipidemia, sedentary life style, obesity, stress and depression. The combination of several risk factors further enhances the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several studies showed the increased risk of ACS in hypercholesterolemia patients [ 39 , 40 ]. Particularly, it had the highest association with non-HDL cholesterol [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the increased risk of ACS in hypercholesterolemia patients [ 39 , 40 ]. Particularly, it had the highest association with non-HDL cholesterol [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, biochemical and instrumental tests are performed within the first six hours of the infarction to confirm the presence of the ischemic event. Some cardiac markers are used to determine a myocardial infarction through biochemical tests and monitoring aspartate, transaminase, alanine transaminase, troponin I and creatine kinase [ 40 ].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Echocardiography is very useful to individuals who have NSTEMI. 8 The indication of the echocardiographic study to evaluate the left ventricular systolic function corresponds to one of the main clinical applications of this diagnostic method. Ventricular contractility represents the result of a complex interaction between the contractile state of the cardiac muscle and the pre-and afterload levels.…”
Section: Different Types Of Diagnostic Resources Usedmentioning
confidence: 99%
“…Ventricular contractility represents the result of a complex interaction between the contractile state of the cardiac muscle and the pre-and afterload levels. 8 Nuclear cardiology is important for individuals who have STEMI, since the information obtained through scintigraphy allows the assessment of myocardial perfusion according to the location of coronary irrigation. Myocardial scintigraphy with physical or pharmacological stress is performed in patients with unstable myocardial ischemic syndromes of low or intermediate risk after resolution of a heightened condition.…”
Section: Different Types Of Diagnostic Resources Usedmentioning
confidence: 99%